2008
DOI: 10.1073/pnas.0705985105
|View full text |Cite
|
Sign up to set email alerts
|

When pliers become fingers in the monkey motor system

Abstract: The capacity to use tools is a fundamental evolutionary achievement. Its essence stands in the capacity to transfer a proximal goal (grasp a tool) to a distal goal (e.g., grasp food). Where and how does this goal transfer occur? Here, we show that, in monkeys trained to use tools, cortical motor neurons, active during hand grasping, also become active during grasping with pliers, as if the pliers were now the hand fingers. This motor embodiment occurs both for normal pliers and for ''reverse pliers,'' an imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
262
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(287 citation statements)
references
References 24 publications
20
262
0
3
Order By: Relevance
“…It has been demonstrated that neurons in areas of the monkey parietal and premotor cortices undergo changes as a consequence of tool use [16,32,33]. In one study, in which monkeys were trained to use different tools to grasp food morsels, it has been found that motor neurons of the ventral premotor cortex, normally active during hand grasping, also fired when the monkeys grasped the food with the tools, regardless of the exact movement sequence required for the purpose [16].…”
Section: Discussion (A) Individual Learning and Understanding Of The mentioning
confidence: 99%
“…It has been demonstrated that neurons in areas of the monkey parietal and premotor cortices undergo changes as a consequence of tool use [16,32,33]. In one study, in which monkeys were trained to use different tools to grasp food morsels, it has been found that motor neurons of the ventral premotor cortex, normally active during hand grasping, also fired when the monkeys grasped the food with the tools, regardless of the exact movement sequence required for the purpose [16].…”
Section: Discussion (A) Individual Learning and Understanding Of The mentioning
confidence: 99%
“…Single-cell studies in monkeys showed that neurons in F5 and PFG can code different aspects of an action: the type of grip and the overall goal of the action, transcending the motor specifics [17,[41][42][43][44][45]. Such responses have been interpreted in terms of how the motor cortex is hierarchically organized in order to allow an agent to visually guide movements in space to reach [19,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…The idea that fronto‐parietal mirror neurons code the goal of an action rather than the action's low‐level kinematics is further supported by a study of Umilta and colleges, showing that different actions having the same goal evoke similar neural response (Umilta et al. 2008). Mirror neurons have also been shown to respond not only to visual input but also to auditory cues associated with motor acts [e.g., the sound of breaking a peanut (Kohler et al.…”
Section: Introductionmentioning
confidence: 99%